2022
DOI: 10.3390/cancers14143491
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Regulatory Protein CBX2 Promotes mTORC1 Signalling and Inhibits DREAM Complex Activity to Drive Breast Cancer Cell Growth

Abstract: Chromobox 2 (CBX2) is a chromatin-binding component of polycomb repressive complex 1, which causes gene silencing. CBX2 expression is elevated in triple-negative breast cancer (TNBC), for which there are few therapeutic options. Here, we aimed to investigate the functional role of CBX2 in TNBC. CBX2 knockdown in TNBC models reduced cell numbers, which was rescued by ectopic expression of wild-type CBX2 but not a chromatin binding-deficient mutant. Blocking CBX2 chromatin interactions using the inhibitor SW2_15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A CBX2 knockout prevented CCND2 expression, and CBX2 showed a negative correlation with CDKN1A , which encodes p21 ( Figure 4I ). This supported CBX2 could pose competition to the DREAM complex [ 29 ]. On particular mechanisms, though, more study is required.…”
Section: Discussionmentioning
confidence: 98%
“…A CBX2 knockout prevented CCND2 expression, and CBX2 showed a negative correlation with CDKN1A , which encodes p21 ( Figure 4I ). This supported CBX2 could pose competition to the DREAM complex [ 29 ]. On particular mechanisms, though, more study is required.…”
Section: Discussionmentioning
confidence: 98%
“…There are various studies about the function of CBX2 in breast cancer. Bilton et al [ 63 ] identified novel mechanisms by which CBX2 promotes breast cancer growth, and inhibition of CBX2 could be a novel therapeutic strategy. Zheng et al [ 64 ] stated that there was a positive correlation between high CBX2 expression and activation of the PI3K/AKT pathway, and that CBX2 could be a potential prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…CBX2, as a component of cPRC1, participates in the epigenetic control of gene expression, leading to chromatin compaction and the suppression of speci c genes [28]. Recent research revealed that CBX2 enhances mTORC1 activity by suppressing mTORC1 inhibitors, and inhibiting CBX2 might reduce TNBC cell growth and viability by inhibiting mTORC1 downstream [29]. Another study demonstrated that silencing CBX2 affected numerous oncogenes in the MAPK signaling pathway in acute myeloid leukemia [30].…”
Section: Discussionmentioning
confidence: 99%